Solar-driven chemical looping methane reforming using zno oxygen carrier for syngas and zn production in a cavity-type solar reactor - Chuayboon, Srirat; Abanades, Stéphane (My University, 2020)
Converting sunlight into chemical fuels and metal commodities, via solar thermochemical conversion processes, is an attractive prospect for the long-term storage of renewable energy. In this study, the combined methane reforming and ZnO reduction in a single reaction for co-production of hydrogen-rich syngas and metallic Zn was demonstrated in a flexible solar thermochemical reactor prototype, driven by highly concentrated sunlight. Using solar energy as the process heat source in chemical-looping methane reforming with the ZnO/Zn oxygen carrier is a means to reduce the dependence on conventional energy resources and to reduce emissions of CO2 and other pollutants, while upgrading the calorific value of the feedstock for the production of energy-intensive and high-value chemical fuels and materials. On-sun experiments were carried out with different operating parameters including operating temperatures (800–1000◦C), inlet methane flow-rates (0.1–0.4 NL/min), and inlet ZnO feeding-rates (0.5–1.0 g/min) both in batch and continuous modes under reduced (0.15 and 0.45 bar) and atmospheric pressures (0.90 bar), thereby demonstrating solar reactor flexibility and reliability. As a result, increasing the temperature promoted net ZnO conversion at the expense of favored methane cracking reaction, which can be lowered by decreasing pressure to vacuum conditions. Diminishing total pressure improved the net ZnO conversion but favored CO2 yield due to insufficient gas residence time. Rising ZnO feeding rate under a constant over-stoichiometric CH4/ZnO molar ratio of 1.5 enhanced ZnO and methane consumption rates, which promoted Zn and syngas yields. However, an excessively high ZnO feeding rate may be detrimental, as ZnO could accumulate when the ZnO feeding rate is higher than the ZnO consumption rate. In comparison, continuous operation demonstrated greater performance regarding higher ZnO conversion (XZnO) and lower methane cracking than batch operation. High-purity metallic Zn with a well-crystallized structure and of micrometric size was produced from both batch and continuous tests under vacuum and atmospheric pressures, demonstrating suitable reactor performance for the solar thermochemical methane-driven ZnO reduction process. The produced Zn metal can be further re-oxidized with H2O or CO2 in an exothermic reaction to produce pure H2 or CO by chemical-looping.
Keywords: Chemical-looping methane reforming; Concentrated solar power; Hydrogen; Metal oxide; Oxygen carrier; Solar reactor; Syngas